A study on the response of a target plate to a foreign object placed at various depths in a cylindrical Charge - Hoare, Matthew (Department of Mechanical Engineering, 2024)
The threat of Improvised Explosive Devices (IEDs) has grown exponentially in the 21st century, as the methods and means of warfare have adapted to modern threats such as terrorism. IEDs are especially damaging and lethal because they are often randomly embedded with a variety of projectiles that consist of readily available items, such as ball bearings, nails or glass. The versatile nature of IEDs makes it very difficult to conduct a generalised study on their impact. One major challenge in IED research is the wide range of potential IED geometries, sizes, explosion types and embedded object configurations. Understanding the behaviour of a simplified IED, consisting of a blast-driven ball bearings embedded in explosive charges, will provide insights into the mechanics of IEDs and its subsequent interactions with a target with a view to developing better protection from IEDs. This dissertation presents the results of a study investigating the damage caused by a simplified IED which consists of a cylindrical explosive charge that was embedded with a single ball bearing. The influence of the placement of a ball bearing along the axis within a rear-detonated cylindrical charge was studied and the placement effects were evaluated in terms of the impact velocity of the ball bearing and its subsequent damage on a Domex 700 steel (also referred to as Strenx in Europe) target plate. Typical deformation of a structure from an IED is a result from of blast loading (pressure wave) and impact loading from the shrapnel/fragment. In this study the combined blast and impact events of a simplified IED were decoupled into separate events to gain a better understanding of the contributions of the different loading conditions. The target plates were exposed to bare charges to quantify the effects on blast loading events. Impact tests were carried out using a two-stage gas gun to relate impact velocity to the deflection of the target plate. Tests were also carried out with explosive charges embedded with a ball bearing at varying depths to analyse the combined event. For all blast tests, the charge diameter was kept constant. Three different charge masses with varying placements of the ball bearing were investigated. Computational simulations, validated using experimental data, were used to elucidate additional details to gain insight about the momentum transfer during the blast event. The results showed similar critical influence of the placement of the ball bearing relative to the charge for the different charge masses used.